ROLE OF TERMINALIA ARJUNA IN ISCHEMIC HEART DISEASE (HRIDAROGA): A REVIEW - Manisha, Dikshit; Puneet Kumar, Garg; G. K., Saxena (International Journal of Ayurveda and Pharma Research, 2015)
Now days, life is becoming very stressful and fast. As many diseases originate due to this hectic lifestyle. One of the important disease is Hridaroga (Ischemic heart disease), which is responsible for many deaths in early age. In Ayurveda, Hridaroga & their symptoms are described in many textbooks. Management of Hridaroga is also very critical and important. In modern medicine, only expensive interventional procedures are described but on the other hand, Ayurvedic herbs are better, cost effective & good therapeutic option for IHD (Hridaroga).The review emphasizes on various properties of Terminalia arjuna. Many clinical & animal studies on T.arjuna show its effect on ECG changes, LV functions & myocardial ischaemic reperfusion injury-etc. Besides this it also has antiatherosclerotic, anticoagulant, anti-infarction, hypolipidemic & hypotensive properties. So, Ayurvedic drug (T. arjuna) is a better option for the treatment of IHD (Hridaroga) because it can improve the quality of life in individuals & potentially save millions of lives.